Some aspects of application of pesticides and fertilizers on nutritive value and other characteristics of crop plants - Nikolić, Bogdan; Waisi, Hadi; Đurović, Sanja; Dugalić, Miloš; Jovanović, Vladan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
We surveyed different aspects of the application of agrochemicals (pesticides and foliarnon-standard fertilizers) on the nutritive value and other non-yield characteristics of cropplants. The survey was based on results of our own trials and studies conducted by otherresearchers. Various parameters of plant and seedling growth, and yield, were analyzed, aswell as the chemical composition, and energetic and thermodynamic parameters of plantsin order to better assess the impact of these agrochemicals on crops. The application ofvarious agrochemicals has been found to affect the germination of seeds produced by treatedplants. The most significant and most diverse results have been obtained by analyzing theyield and yield components of many different crops (field crops, fruits, vegetables), as well astheir chemical composition (mineral elements, different sugars, secondary metabolites, etc.)in terms of improving their nutritive quality. It was found that in maize seedlings it occurs bychanging the content of various elements, as well as polyphenol profiles and thermodynamicparameters, and the effects did not only depend on the dosage of agrochemicals but also onmaize genotype. We also found that agrochemicals affected the energetic and thermodynamicparameters of individual maize plants, as well as the parameters of plant growth and yield. Itwas noticed that these agrochemicals greatly affected the content of microelements, starchand crude proteins in maize and barley, sugar and polyphenol contents in various fruit treesand soybean. We noted that in certain agroecological situations these agrochemicals haveled to spectacular magnification of yields of different crops, but there were also situationswhen they did not have any positive effect on crop yield, which is discussed also in thecontext of results of other researchers.
Keywords: pesticides; fertilizers; crop plants; yield; nutritional quality; plant stress